The Emperors' New Gifts: Bestowing Sacrificial Necessities and Burial Essentials in Ming Dynasty (1368–1644) China. (2nd January 2019) - Jin, Hui-Han
Abstract : The tradition of granting funerary gifts from the emperor to his prominent ministers can be traced back to the Zhou dynasty. Scholars have agreed that the gifts meant more than assistance in preparing death rituals but were regarded as an honor to the deceased. What has been less discussed in recent scholarship is the role the emperor perceived himself as playing in the death rituals of his ministers through the types of funerary gifts he offered. A dramatic change in the types of funerary gifts bestowed was initiated by the Hongwu Emperor (1368–1398), and this new practice was continued by the subsequent emperors. By looking into the purpose of granting the new gifts and the ways of bestowing them, both of which had changed over the course of the Ming dynasty, we will be able to scrutinize the dynamic relationships between monarchs and officials through the conflicts between emotions and rituals and the adaptability of Confucian prescriptions and practices.